Miracles of Numbers, 3, 6, And 9 Numbers - Belay Sitotaw Goshu; Syarifuddin (Britain International for Academic Research (BIAR) Publisher, 2024)
The physical and energy forms and patterns of creation are intrinsically tied to the numbers 3, 6, and 9. Each number corresponds to a different stage of creation, with sets of three and nine (33) denoting stage completion. The sets of three consistently lead us to the same order: 12 (3), 15 (6), 18 (9), 21 (3), 24 (6), 27 (9), 30 (3), 33 (6), and 36 (9). The goal is to investigate the wonder of numbers 3, 6, and 9 from science, religion, and human perception. 111 (3), 222 (6), 333 (9), 444 (12)3, 555 (15-6), 666 (18-9), 777 (21)3, 888 (24-6), and 999 (27-9) are among the triple numbers that appear in this order. It also repeats on the frequencies listed below, which are thought to be ancient healing frequencies: 147 hertz (12-3) - 258 hertz (15-6) - 369 hertz (18-9) - 471 hertz (12-3), 582 Hz (15-6), 693 Hz (18-9), 714 Hz (12-3), 825 Hz (15-6), and 936 Hz (18-9). The analysis demonstrates from both a scientific and religious standpoint.